Cryptic species composition and genetic diversity within Bemisia tabaci complex in soybean in India revealed by mtCOI DNA sequence - H C Prasanna; S Kanakala; K Archana; P Jyothsna; R K Varma; V G Malathi (Journal of Integrative Agriculture, 2015)
Bemisia tabaci is a cryptic species complex, causing significant loss on many agriculturally important crops worldwide. Knowledge on species composition and diversity within B. tabaci complex is critical for evolving sustainable pest management strategies. Here we investigate the whitefly species complex in soybean in major soybean growing states of India. The mitochondrial cytochrome oxidase gene subunit-1 (mtCOI) based phylogenetic relationships established using Bayesian methods indicated the existence of three cryptic species namely Asia I, Asia II 1, and Asia II 7. All the haplotypes detected in the study could be assigned to these three cryptic species following the species demarcation criteria of 3.5% divergence threshold. Of these, Asia II 1 was found to be predominant with wide spread distribution across the surveyed regions from cool temperate zones to hot and humid tropical plains. On the contrary, cryptic species Asia II 7 showed localized distribution. The Asia II 1 exhibited the highest haplotype diversity and Asia I showed high level of nucleotide diversity. There was a significantly high genetic differentiation among these three cryptic species. The MEAM 1, a dreadful invasive species was not detected in the specimens tested in the current study. The diversity and distribution of three cryptic species is discussed in the light of current knowledge on distribution of whitefly species in India and yellow mosaic disease observed during sampling survey.